-5(5s+2)+3(s-4)=

Simple and best practice solution for -5(5s+2)+3(s-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(5s+2)+3(s-4)= equation:


Simplifying
-5(5s + 2) + 3(s + -4) = 0

Reorder the terms:
-5(2 + 5s) + 3(s + -4) = 0
(2 * -5 + 5s * -5) + 3(s + -4) = 0
(-10 + -25s) + 3(s + -4) = 0

Reorder the terms:
-10 + -25s + 3(-4 + s) = 0
-10 + -25s + (-4 * 3 + s * 3) = 0
-10 + -25s + (-12 + 3s) = 0

Reorder the terms:
-10 + -12 + -25s + 3s = 0

Combine like terms: -10 + -12 = -22
-22 + -25s + 3s = 0

Combine like terms: -25s + 3s = -22s
-22 + -22s = 0

Solving
-22 + -22s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + -22s = 0 + 22

Combine like terms: -22 + 22 = 0
0 + -22s = 0 + 22
-22s = 0 + 22

Combine like terms: 0 + 22 = 22
-22s = 22

Divide each side by '-22'.
s = -1

Simplifying
s = -1

See similar equations:

| 39=-2w-3w-26 | | 36x^2-36x-16=0 | | 3|b|=21 | | 4q+106+q+20=180 | | 9c+2d-4(8c-8d)= | | 3y+4y-29=-71 | | 3x^2+10+15x+20=180 | | 5y-1+y+13=8y+20-6y | | 9a+10(6a-1)=equation | | 2(4x-3.7)=3x-7.4 | | 10-5(9n-9)=equation | | 3x+9+3(2x-6)= | | 8x^3+28x^2+88x=0 | | 3s-18=-10+s | | -5n+3(6+7n)=equation | | 200x-0.03=400x+0.79 | | 14x=y | | 7(1-3m)-4=equation | | 3.2=5x+5.4 | | 8x^3-6x^2-18x+16=0 | | 12x+5+3x-5=equation | | x+89=2x-17+x+1 | | (x^2-9x+3)(9x^2+3x+3)= | | 2.3x=-14.49 | | n+4-9+7n=equation | | -5(4m+8)=-5(-7-m) | | -5(4m+8)=-5(-7m-m) | | x-27x=36 | | -5(4+8)=-5(-7m-m) | | (-x^2+3x)-(5x+2x^2)=0 | | 2x^2+4x-160= | | -2x+11+6x=equation |

Equations solver categories